Automation algorithm of the information search and fixation in unformalized messages for the management of socially significant intelligent projects - Darkhan O. Zhaxybayev; Murat N. Bakiyev (Вестник ВГУ. Серия: Системный анализ и информационные технологии, 2022)
The article discusses the importance of automation for managing the intelligent processes and evaluating the effectiveness of processes. Often this process requires the creative approach of an analyst who has to read a lot of media information relating to the crowdsourcing project activity. This may be messages from users, persons concerned, experts` comments and other information generated by society as a response to the project activity. For many reasons, this is a non-optimal process, firstly, an analyst must review the entire array of information to estimate the project activity, and it is difficult to parallel this task. Since the social situation is subject to variation just for several hours and the human factor keeps away from such efficiency, then the evaluation relevance and up-to-dateness are compromised. It is necessary to automate the evaluation process of the crowdsourcing activity and this is the essence of our approach. We have developed the hierarchic thesaurus for highlighting the information from users` and persons` concerned messages, in the press reports and blog comments. Findings show that crowdfunding projects are hybrid in nature and include the elements of crowdsourcing, crowdsensing, crowdfunding, crowdworking, and crowdsourced recruitment. We explored the possibility of automating the efficiency evaluation of various crowdsourcing working processes and proposed design solutions for the development of such systems. Thе preliminary results indicate that leading issues include the lack of financial guarantees and the likelihood of information leakage to competitors. Hence, the first priority is to manage the exchange of money and information. By following this strategy, the crowdsourcing platforms will reach a high level of responsibility among project initiators and participants and will reduce the likelihood of tax avoidance by individuals, who received a financial reward.